In vitro activity of four triazole antifungal drugs against clinically common and uncommon yeast species - Narges Aslani; Tahereh Shokohi; Mohammad Reza Ataollahi; Saham Ansari; Yousef Gholampour; Ali Khani Jeihooni; Mohammad hosein Afsarian (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Incidence of fungal infections caused by opportunistic fungal pathogens, such as yeasts and yeast-like species, has undergone an increase in otherwise healthy individuals. These pathogens account for high mortality and show reduced susceptibility to the routine antifungal drugs. Accordingly, antifungal susceptibility testing is an urgent need in the determination of the susceptibility spectrum of antifungals and selection of appropriate antifungal agents for the management of patients with fungal infection. Materials and Methods: The present study was conducted on 110 yeast strains belonging to 15 species recovered from clinical specimens. Susceptibility of the isolates to four antifungal drugs (i.e., fluconazole, itraconazole, voriconazole, and posaconazole) was tested according to the Clinical and Laboratory Standards Institute guidelines M27-A3 and M27-S4. Results: Fluconazole exhibited no activity against 4.3% (n=2) of C. albicans isolates, whereas the remaining 44 isolates had a minimum inhibitory concentration (MIC) range of 0.125-4 μg/ml. Voriconazole had the lowest geometric mean MIC (0.03 μg/ml) against all isolated yeast species, followed by posaconazole (0.07 μg/ml), itraconazole (0.10 μg/ml), and fluconazole (0.60 μg/ml). Overall, all of the isolates had reduced voriconazole MICs with a MIC range of 0.016-0.5 μg/ml, except for one isolate of C. albicans that had a MIC of 1 μg/ml. Candida haemulonii as a multidrug-resistant fungus showed a fluconazole MIC of > 64 μg/ml. Conclusion: The current study provides insight into the antifungal susceptibility profiles of clinically common and uncommon yeast species to four triazole antifungal agents. According to our findings, voriconazole was the most active agent. Awareness about antifungal susceptibility patterns is highly helpful in the selection of appropriate antifungal drugs and identification of the efficiency of the currently used agents.